Pelatihan Senam Kreasi Anak untuk Meningkatkan Daya Ingat, Konsentrasi, dan Kebugaran Jasmani Siswa MI di Sidoarjo - Nadia Marta Trilova (PT. Adriani Mandiri Publisher, 2026)
This Community Service activity aims to improve memory, focus, and physical fitness of elementary school students in Bakalan Wringin Pitu Village. The background of the activity is the low physical activity of students and decreased concentration due to the dominance of passive activities such as the use of gadgets. The method used is the Asset Based Community Development approach with the stages of planning, implementation, and evaluation. Data were collected through observation, interviews, and questionnaires. The activity was carried out through warm-ups, core movements, and cool-downs accompanied by music and structured movement repetition. The results showed an increase in student active participation, the ability to remember the sequence of movements, and concentration during the activity. In addition, there was an increase in physical fitness and gross motor skills. The interaction between students and teachers created a fun and collaborative learning atmosphere. This activity also contributed to character development such as discipline, self-confidence, and cooperation. Overall, the children's creative gymnastics program is effective as an innovative learning method that integrates cognitive, physical, and social aspects. This program has the potential to be implemented sustainably to support the quality of learning and optimal student health in the elementary school environment broadly and continuously for the overall development of students in the long term that is better and highly competitive in a productive and healthy future consistently and sustainably for all students who are actively involved